1981
DOI: 10.1021/i200012a020
|View full text |Cite
|
Sign up to set email alerts
|

Safety aspects of organic peroxides in bulk tanks

Abstract: The dangers associated with the handling of organic peroxides in bulk quantities of the order of 10 m3 are analyzed. The possible sequence of events in case of an accident is enumerated. The worst probable situations have experimentally been simulated in 33 X 10"3 m3 and 234 X 10"3 m3 model tank investigations. Many experiments have been carried out to cover the maximal hazardous effects of an organic peroxide decomposing in a tank equipped with venting devices. Product temperature course and pressures inside … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…No vent sizing criterion that would take vapour influence into account is available although it was demonstrated that it greatly modifies the necessary vent size [6], [7], [8], [9] and [10]. Few experiments involving the runaway and blowdown of non tempered systems were published [11], [12], [13], [14] and [15]. These tests were performed with the objective of developing the UN 10 l method based on the similarity principle.…”
mentioning
confidence: 99%
“…No vent sizing criterion that would take vapour influence into account is available although it was demonstrated that it greatly modifies the necessary vent size [6], [7], [8], [9] and [10]. Few experiments involving the runaway and blowdown of non tempered systems were published [11], [12], [13], [14] and [15]. These tests were performed with the objective of developing the UN 10 l method based on the similarity principle.…”
mentioning
confidence: 99%